Perancangan UI/UX untuk Optimalisasi Booking Online dalam meningkatkan Potensi Wisata Daerah Leuwi Asih - Humam Mu'asyir; Tundo; Husain Rahmani; Muhammad Derry Oktaviandi (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
UI/ UX Design for development of online booking technology and digital tour guides in the Leuwi Asih tourist area aims to increase regional tourism potential through web-based services. This system is designed to make it easy for tourists to make reservations and get information related to tourist destinations efficiently. This research uses a qualitative method by collecting data through direct interviews with local residents and local tourism business owners. The result of this research is a website that functions as a platform to facilitate the management of tourist reservations and provide digital tourist information. Thus, this system is able to support the development of local tourism and improve the tourist experience significantly.